Regulasi Diri sebagai Prediktor Fear of Missing Out - Zahra Parameita, Salsa; Rahmawati, Agustin; Juliadilla, Risa (Inquiry: Jurnal Ilmiah Psikologi, 2025)
Fear of Missing Out (FoMO) has become a phenomenon frequently experienced by female college students, causing individuals to access social media addictively due to the fear of missing out on moments. The impacts of FoMO include decreased academic performance, low life satisfaction, and even depression. To reduce the occurrence of FoMO, female students need to have good self-regulation skills to stay focused on academic activities and avoid addictive use of social media. The purpose of this study is to determine whether there is an effect of self-regulation on FoMO among female college students who use social media. The hypothesis of this study is that self-regulation affects FoMO among female social media users at University of Merdeka Malang. The population consisted of 4,010 female social media users, with a sample of 100 female social media users at University of Merdeka Malang, selected using purposive sampling. The measurement instruments used were the FoMO scale and the self-regulation scale. Hypothesis testing using simple linear regression analysis showed a significance value of 0.018 < 0.05. Self-regulation influenced FoMO by 5%. The higher the level of self-regulation, the lower the level of FoMO, and vice versa. These findings can be applied to the development of self-regulation training programs in higher education to reduce excessive social media use and lower FoMO levels among students.